Graduation day! - Ransom, Candice F., 1952-; Evans, Ashley (2023)
Raymond prepares for his graduation day using all of the skills he has learned throughout the year.
Keywords: Stories in rhyme; Graduation (School) -- Fiction; Stories in rhyme; Picture books